Dietary wood pulp-derived sterols modulation of cholesterol metabolism and gut microbiota in high-fat-diet-fed hamsters. Issue 2 (22nd January 2019) - Li, Xiang; Wang, Huali; Wang, Tianxin; Zheng, Fuping; Wang, Hao; Wang, Chengtao
Abstract : Wood pulp-derived sterols (WS) supplementation ameliorated HFD-associated metabolic disorder; WS supplementation increased the amounts of fecal sterols excretion and SCFAs content; WS supplementation modulated gut microbiota composition. Abstract : Evidence indicates that wood pulp-derived sterols (WS) have beneficial effects on cardiovascular diseases. The present study aimed to (i) investigate the serum cholesterol-lowering activity of dietary WS and (ii) investigate the effects of dietary WS on the balance of gut microbiota in hamsters fed with a high-fat diet. Thirty-six hamsters were divided into four groups fed on a normal chow diet (NCD), a high-fat diet (HFD), or HFD plus 0.1% or 0.5% wood pulp-derived sterols (WSL, WSH), respectively, for 6 weeks. Levels of serum total cholesterol, triglyceride, HDL-C, non-HDL-C, and non-HDL-C/HDL-C ratio in hamsters fed the NCD were originally 120.4 mg dL −1, 235.8 mg dL −1, 71.7 mg dL −1, 48.7 mg dL −1 and 0.68 mg dL −1, which were elevated by being fed the HFD to 187.7 mg dL −1, 389.5 mg dL −1, 92.3 mg dL −1, 95.3 mg dL −1 and 1.03 mg dL −1, and alleviated completely by being fed the WSH. The excretion of total fecal neutral sterols was dose-dependently increased with the amounts of dietary WS. Furthermore, dietary supplementation with WS modulated the relative abundance of gut microbiota compared with the HFD group. Spearman's correlation analysis revealed that Bacteroides, Allobaculum, Coprobacillus, Lactobacillus, Akkermansia, Coprococcus, and Oscillospira were correlated negatively with most of the serum metabolic parameters and cholesterol metabolic parameters, whereas Desulfovibrio was positively correlated with most of the lipid metabolism-associated parameters. Taken together, dietary supplementation with WS was found to have cholesterol-lowering activity, in part mediated by modulating the gut microbiota in a positive way and regulating the cholesterol absorption and metabolism-related genes.